Impact of Aging on the Frequency, Phenotype, and Function of CD161-Expressing T Cells - van der Geest, Kornelis S. M.; Kroesen, Bart-Jan; Horst, Gerda; Abdulahad, Wayel H.; Brouwer, Elisabeth; Boots, Annemieke M. H. (Frontiers in Immunology, 2018)
Immune-aging is associated with perturbed immune responses in the elderly. CD161 expressing T cells, i.e. the previously described subsets of CD161+CD4+ T cells, CD161highCD8+ T cells and CD161intCD8+ T cells, are highly functional, pro-inflammatory T cells. These CD161 expressing T cells are critical in immunity against microbes, while possibly contributing to autoimmune diseases. So far, little is known about the impact of aging on the frequency, phenotype and function of these CD161 expressing T cells. In the current study, we investigated the impact of aging on CD161+CD4+ T cells, CD161highCD8+ T cells and CD161intCD8+ T cells in peripheral blood samples of 96 healthy subjects (age 20-84). Frequencies of CD161+CD4+ T cells and CD161intCD8+ T cells were stable with aging, whereas frequencies of CD161highCD8+ T cells declined. Although CD161highCD8+ T cells were mostly TCR-Vα7.2+ mucosal-associated invariant T cells, CD161 expressing CD4+ and CD8+ T cells showed limited expression of markers for gamma-delta T cells or invariant natural killer T cells, both in young and old subjects. In essence, CD161 expressing T cells showed a similar memory phenotype in young and old subjects. Expression of the inhibitory natural killer receptor KLRG1 was decreased on CD161+CD4+ T cells of old subjects, whereas expression of other natural killer receptors by CD161 expressing T cells was unaltered with age. Expression of cytotoxic effector molecules was similar in CD161high and CD161intCD8+ T cells of young and old subjects. The ability to produce pro-inflammatory cytokines was preserved in CD161high and CD161intCD8+ T cells of old subjects. However, percentages of IFN-γ+ and IL-17+ cells were significantly lower in CD161+CD4+ T cells of old individuals than those of young individuals. In addition, aging was associated with a decrease of non-classic T helper 1 cells, as indicated by decreased percentages of CD161 expressing cells within the IFN-γ+ CD4+ T cell compartment of old subjects. Taken together, aging is associated with a numerical decline of circulating CD161highCD8+ T cells, as well as a decreased production of pro-inflammatory cytokines by CD161+CD4+ T cells. These aging-associated changes could contribute to perturbed immunity in the elderly.